Dermatological practice in Turkic-Mongolian folk medicine: cult of fire and the phenomenon of healing - Sodnompilova, Марина (Turkic Studies Journal, 2021)
The article discusses the traditional ideas of the Turkic-Mongolian peoples about dermatological lesions and other skin diseases as well as methods and techniques for their treatment. On the basis of rich historical, ethnographic and folklore material, the specific causes of such diseases are revealed, primarily those associated with the fire of the home, and on the other hand, sent by cult animals (wolf / dog) and birds (eagle, raven) in revenge for the evil done. The author pays attention to the description of the image of folk healers endowed with exclusive rights in the treatment of skin diseases. The conceptual provisions of the article make it possible, through the prism of traditional medical knowledge, to identify the common sources of life and worldview systems of the Turkic-Mongolian peoples.